2011
DOI: 10.1097/jgp.0b013e3181ff416c
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of DSM-IV Symptom and Clinical Significance Criteria on the Prevalence Estimates of Subthreshold and Threshold Anxiety in the Older Adult Population

Abstract: Objectives-Subthreshold anxiety refers to a condition where individuals do not meet the full symptom criteria (i.e., the number of symptoms required for a formal diagnosis is not reached) and/or do not report significant impairment or distress in functioning (i.e., the clinical significance criterion is not met). The purpose of this study was to examine how the symptom and the clinical significance criteria may affect the prevalence estimates of anxiety problems in the older adult population and whether applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
86
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 39 publications
6
86
1
4
Order By: Relevance
“…Although the occurrence of increased levels of anxiety (score above cutoff) is similar, complete absence of anxiety symptoms is infrequently reported by older people with ID, regardless of higher psychotropic drug use. Being single and low education levels are related to anxiety, 22,36 which might explain the more frequent occurrence of anxiety symptoms in this group, because most were single and did not complete elementary education. We have recently shown that the prevalence of major depression is much higher in older people with ID than in the general older population, and it is highly correlated with anxiety.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the occurrence of increased levels of anxiety (score above cutoff) is similar, complete absence of anxiety symptoms is infrequently reported by older people with ID, regardless of higher psychotropic drug use. Being single and low education levels are related to anxiety, 22,36 which might explain the more frequent occurrence of anxiety symptoms in this group, because most were single and did not complete elementary education. We have recently shown that the prevalence of major depression is much higher in older people with ID than in the general older population, and it is highly correlated with anxiety.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to determine if older people with ID are more vulnerable to developing symptoms of anxiety. Grenier et al 22 found that older people who reported anxiety symptoms (not meeting symptom criteria for an anxiety disorder) reported more chronic physical health problems and depressive disorders than older people without symptoms of anxiety. Moreover, the incidence of these chronic health problems and depression was similar to that in older people with a full anxiety disorder.…”
mentioning
confidence: 98%
“…Note that the impairment criterion was similar to the other ratings, in that it was based on subjective reports rather than on clinical assessments. The impairment criterion is a component of the current psychiatric classification systems, but it has been previously questioned for certain diagnosis categories, such as anxiety disorders [18,19]. We suggest either omitting the psychiatric impairment criterion in general, or adapting for AjD in particular (''significant deterioration in social and occupational functioning'').…”
Section: Discussionmentioning
confidence: 99%
“…However older adults experience significant functional impairment from sub-threshold anxiety [3], and this can create equal burden on primary care when compared to older people who have a diagnosable anxiety disorder [1] [4].…”
Section: Introductionmentioning
confidence: 99%